2011
DOI: 10.1080/02786826.2010.550961
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic and Mobility Size Distribution Measurements to Reveal Biodiesel Effects on Diesel Exhaust Aerosol

Abstract: This article examines the effect of biodiesel blends on the exhaust aerosol from a Euro 3 passenger car. Five different feedstock oils (soybean, palm, sunflower, rapeseed, and used frying oil) were used to produce fuels with 10% vol. content in biodiesel (B10). Use of the B10 blends led to a systematic reduction of PM mass emissions in the range of ∼9% (rapeseed) to 23% (used frying oil) on average. The combination of particle size distributions based on the aerodynamic and the mobility diameters led to the es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 26 publications
2
8
0
1
Order By: Relevance
“…In addition, a slight decrease in the particle concentrations and mean particle diameter can be observed with biodiesel fueling, which is consistent with other studies. 20,32,45 These results are consistent with the trends of the number of primary particles presented in Figure 4. For 60% load before the thermodenuder, the nucleation mode peaks dominate the particle size distribution.…”
Section: Morphology Analysissupporting
confidence: 87%
“…In addition, a slight decrease in the particle concentrations and mean particle diameter can be observed with biodiesel fueling, which is consistent with other studies. 20,32,45 These results are consistent with the trends of the number of primary particles presented in Figure 4. For 60% load before the thermodenuder, the nucleation mode peaks dominate the particle size distribution.…”
Section: Morphology Analysissupporting
confidence: 87%
“…[18,19] Furthermore, the higher oxygen content in biodiesel may lead to more reactive semi-volatile species and PM with greater oxidative potential. [2022] For instance, some studies have reported that biodiesel PM is more reactive and affects lung cells to a greater degree than petroleum-based fuels.…”
Section: Introductionmentioning
confidence: 99%
“…12 Health problems include increased risk of reduced lung function, adverse respiratory symptoms, asthma, cardiovascular diseases, morbidity, and mortality. 3,[10][11][12][13][14][15] Diesel engine exhaust particles are very complex geometrically, being mainly composed by black carbon/ soot. They are principally formed during combustion in the fuel rich regime of a combustion chamber.…”
Section: Introductionmentioning
confidence: 99%